2017
DOI: 10.1177/1010428317698338
|View full text |Cite
|
Sign up to set email alerts
|

ATP citrate lyase is increased in human breast cancer, depletion of which promotes apoptosis

Abstract: Breast cancer is a malignant tumor that is harmful to women's health around the world. Investigating the biological mechanism is, therefore, of pivotal importance to improve patients' prognoses. Compared to non-neoplastic tissues, enhanced glucose and lipid metabolism is one of the most common properties of malignant breast cancer. Adenosine triphosphate (ATP) citrate lyase is a key enzyme linking aerobic glycolysis and fatty acid synthesis and is of high biological and prognostic significance in breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 47 publications
(60 reference statements)
1
36
0
Order By: Relevance
“…Previous research has reported that the inhibition of ACC reduces tumor growth of pancreatic cancer xenografted in animal models [11] and increases apoptosis in glioblastoma cell lines [12]. Following small interfering RNAmediated inhibition of ACLY in MCF-7 breast cancer cells, cell viability was suppressed and cell apoptosis was increased [13]. Additional supporting evidence to verify the DNL pathway in regulating cancer cell viability has been shown where the inhibition of FASN by FASN inhibitor-alcohol extract of clove suppressed the S-phase DNA replication of HepG2 cells [14].…”
mentioning
confidence: 97%
“…Previous research has reported that the inhibition of ACC reduces tumor growth of pancreatic cancer xenografted in animal models [11] and increases apoptosis in glioblastoma cell lines [12]. Following small interfering RNAmediated inhibition of ACLY in MCF-7 breast cancer cells, cell viability was suppressed and cell apoptosis was increased [13]. Additional supporting evidence to verify the DNL pathway in regulating cancer cell viability has been shown where the inhibition of FASN by FASN inhibitor-alcohol extract of clove suppressed the S-phase DNA replication of HepG2 cells [14].…”
mentioning
confidence: 97%
“…In the latter case, the dependence of tumors on glucose for energy makes ACLY inhibition especially appealing. ACLY knockdown can drastically decrease cancer cell proliferation without significantly affecting nearby healthy tissue (30,31). ACLY may also be a target for anti-aging studies, because decreased nucleocytosolic acetyl-…”
Section: Discussionmentioning
confidence: 99%
“…It is anticipated that 25% of the world's population will have at least one type of cancer in 2030 (Talib, Al‐hadid, Ali, Al‐Yasari, & Ali, 2018). Breast cancer (BC) is one of the major causes of female cancer‐related death (Wang, Yin, Wei, Yang, & Jiang, 2017). It is estimated that 3,131,440 females living in the United States have BC (Talib et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that cancer is not only a genetic disease but also a metabolic disorder (Wang et al, 2017). Metabolic reprogramming is one of the hallmarks of cancer cells that supply the energy and the (macro‐) molecules required for their rapid proliferation (Brohée et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation